Photodynamic Therapy to Eradicate Tumor Cells - Pavarina, Ana Cláudia; Ribeiro, Ana Paula Dias; Dovigo, Lívia Nordi; Andrade, Cleverton Roberto de; Costa, Carlos Alberto de Souza; Vergani, Carlos Eduardo (IntechOpen, 2012)
None